From Incompatibility to Incommensurability: Notes on Isaiah Berlin’s Value Pluralism (Global Journal of Human-Social Science, 2021)
The contemporary public debate is permeated by diverse challenges to social life especially because of the plurality of groups and convictions that are articulated in decision-making spaces In Western societies because of the process of secularization there are no more exclusive systems of values that are capable of giving full meaning to the human experience in the community From the context of the diversity of beliefs and values this paper research discusses the thought of the Russian- Jewish philosopher and historian of ideas Isaiah Berlin 1909-1997 who developed a doctrine of value pluralism For Berlin a notable advocate of liberalism and one of the leading intellectuals of the twentieth century pluralism is a principle of crucial importance for contemporary society as it postulates the coexistence of different systems of moral values and conceptions of good without trying to escape of the inevitable conflict between such values and conceptions
Keywords: isaiah berlin; value pluralism; religion and politics; religion and contemporaneity